2010
DOI: 10.1258/jms.2010.010017
|View full text |Cite
|
Sign up to set email alerts
|

A Fall-off in Cervical Screening Coverage of Younger Women in Developed Countries

Abstract: There is a general trend in developed countries towards lower coverage in young women (25-29 years old). No common underlying cause has been clearly identified and there is a need for further studies to investigate the possible reasons for this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 2 publications
3
41
1
Order By: Relevance
“…2 Similar trends have been noted in other countries including Australia, Canada, Sweden, Denmark, France and Italy. 3 Because the incidence of cervical cancer is highest in women in their thirties, 4 nonattendance for screening in young women has the potential to lead to diagnosis at a later stage of cancer and to poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Similar trends have been noted in other countries including Australia, Canada, Sweden, Denmark, France and Italy. 3 Because the incidence of cervical cancer is highest in women in their thirties, 4 nonattendance for screening in young women has the potential to lead to diagnosis at a later stage of cancer and to poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining uptake in other national programmes demonstrate lower coverage in those most at risk. For example, in the cervical screening programme in England, data show a fall to two-thirds uptake of smears in women, aged 25–29 in the last five years, compared with 75% in 2001,9 when the highest incidence of cervical cancer is in women in their thirties10 and the average time for progression of severe precancerous lesions to invasive cervical cancer is estimated to be 10–15 years 11. Uptake of cervical screening is also consistently lower in areas of lower socioeconomic status 3.…”
Section: Introductionmentioning
confidence: 99%
“…However, cervical screening participation by young women was already gradually declining over the past decade in Australia and other countries. 11 There has been concern that the availability of the vaccine might exacerbate the decline in young women's cervical screening rates, given the potential for women to misunderstand the limitations of the vaccine. A Victorian population study showed that among young, unvaccinated women, only 62.5% realized that the vaccine could not be used to treat cervical cancer or abnormalities.…”
Section: Introductionmentioning
confidence: 99%